ANALISIS KEMAMPUAN LITERASI MATEMATIKA SISWA KELAS X MELALUI KOMIKA PADA MATERI BENTUK ALJABAR DI SMA NEGERI 1 SINTANG - Melinda Rismawati; Marli Hidayat; Anggista Septiani Saputri (Universitas Negeri Jakarta, 2022)
The purpose of this study was to produce comic-based teaching materials in algebraic forms to improve students' literacy skills. This study aims to: 1) Describe the procedure for developing comic-based teaching materials on algebraic materials to improve students' literacy skills. 2) Improve students' literacy skills after using comic-based teaching materials. 3) Knowing the responses of students and teachers to the use of comic-based teaching materials in algebraic forms to improve students' literacy skills. The research method used is R&D. The research site is at SMAN I Sintang. The assessment of mathematical literacy abilities of students in class X IPS 1 SMAN 1 Sintang is high with an average score of 71.08% at the level of problem solving and mathematical reasoning abilities. Meanwhile, the teacher's response based on the teacher's response questionnaire analysis had an average value of 75% with interpretation criteria, and student responses based on the results of the student response questionnaire analysis had an average value of 79.75% with interpretation criteria.Soit can be concluded that the development of learning media carried out is declared feasible, interesting and effective to use in learning